Inhibition of integrin αvβ6 sparks T-cell antitumor response and enhances immune checkpoint blockade therapy in colorectal cancer. Issue 2 (7th February 2022) - Busenhart, Philipp; Montalban-Arques, Ana; Katkeviciute, Egle; Morsy, Yasser; Van Passen, Chiara; Hering, Larissa; Atrott, Kirstin; Lang, Silvia; Garzon, Jesus Francisco Glaus; Naschberger, Elisabeth; Hartmann, Arndt; Rogler, Gerhard; et al.
Abstract : Background: Integrin αvβ6 is a heterodimeric cell surface protein whose cellular expression is determined by the availability of the integrin β6 subunit (ITGB6). It is expressed at very low levels in most organs during tissue homeostasis but shows highly upregulated expression during the process of tumorigenesis in many cancers of epithelial origin. Notably, enhanced expression of integrin αvβ6 is associated with aggressive disease and poor prognosis in numerous carcinoma entities. Integrin αvβ6 is one of the major physiological activators of transforming growth factor-β (TGF-β), which has been shown to inhibit the antitumor T-cell response and cause resistance to immunotherapy in mouse models of colorectal and mammary cancer. In this study, we investigated the effect of ITGB6 expression and antibody-mediated integrin αvβ6 inhibition on the tumor immune response in colorectal cancer. Methods: Using orthotopic and heterotopic tumor cell injection, we assessed the effect of ITGB6 on tumor growth and tumor immune response in wild type mice, mice with defective TGF-β signaling, and mice treated with anti-integrin αvβ6 antibodies. To examine the effect of ITGB6 in human colorectal cancer, we analyzed RNAseq data from the colon adenocarcinoma dataset of The Cancer Genome Atlas (TCGA-COAD). Results: We demonstrate that expression of ITGB6 is an immune evasion strategy in colorectal cancer, causing inhibition of the antitumor immune response and resistance to immune checkpoint blockade therapy by activating latent TGF-β. Antibody-mediated inhibition of integrin αvβ6 sparked a potent cytotoxic T-cell response and overcame resistance to programmed cell death protein 1 (PD-1) blockade therapy in ITGB6 expressing tumors, provoking a drastic increase in anti-PD-1 treatment efficacy. Further, we show that the majority of tumors in patients with colorectal cancer express sufficient ITGB6 to provoke inhibition of the cytotoxic T-cell response, indicating that most patients could benefit from integrin αvβ6 blockade therapy. Conclusions: These findings propose inhibition of integrin αvβ6 as a promising new therapy for colorectal cancer, which blocks tumor-promoting TGF-β activation, prevents tumor exclusion of cytotoxic T-cells and enhances the efficacy of immune checkpoint blockade therapy.